Regulatory microRNA - Taguchi, Y-h (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This book includes updated information about microRNA regulation, for example, in the fields of circular RNAs, multiomics analysis, biomarkers and oncogenes. The variety of topics included in this book reaffirms the extent to which microRNA regulation affects biological processes. Although microRNAs are not translated to proteins, their importance for biological processes is not less than proteins. An understanding of their roles in various biological processes is critical to understanding gene function in these biological processes. Although non-coding RNAs other than microRNAs have recently come under investigation, microRNA still remains the front runner as the subject of genetic and biological studies. In reading the collection of papers, readers can grasp the most updated information regarding microRNA regulation, which will continue to be an important topic in genetics and biology.